Prawna koncepcja kierowania na tle rozwoju resortowego systemu zarządzania przemysłem państwowym w PRL: [Legal conception of administration in the light of departmental system of management of industry in the Polish People's Republic] (Studia Prawnicze / The Legal Studies, 1983)
One of the basic problems in forming legal grounds for the system of management of state economy is administration of state economic organizations. A term „to administer" has been used by the legislator as well as the legal science. As it has not been defined by the law, in practice and theory different legal meanings are attached to it. The aim of the analysis was to define legal content of the notion „to administer".The research was carried out on fundamental legal acts and legal acts by chief organs of state administration defining structure and functioning of state economy since 1945.